2005
DOI: 10.1111/j.1462-2920.2005.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylation is the initial reaction in anaerobic naphthalene degradation by a sulfate‐reducing enrichment culture

Abstract: The sulfate-reducing culture N47 can utilize naphthalene or 2-methylnaphthalene as the sole carbon source and electron donor. Here we show that the initial reaction in the naphthalene degradation pathway is a methylation to 2-methylnaphthalene which then undergoes the subsequent oxidation to the central metabolite 2-naphthoic acid, ring reduction and cleavage. Specific metabolites occurring exclusively during anaerobic degradation of 2-methylnaphthalene were detected during growth on naphthalene, i.e. naphthyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 35 publications
(46 reference statements)
1
66
1
Order By: Relevance
“…Another naphthalene-degrading sulfate-reducing enrichment obtained from an oilcontaminated aquifer initially showed the same pattern Meckenstock et al, 2000). However, a more recent study with the same culture and deuterated naphthalene demonstrated that the initial attack on the parent substrate was methylation to 2-methylnaphthalene, which was subsequently oxidized to 2-naphthoic acid via a fumarate addition reaction (Safinowski and Meckenstock, 2006). The report of naphthalene methylation resembles the recently described methylation of benzene (Ulrich et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Another naphthalene-degrading sulfate-reducing enrichment obtained from an oilcontaminated aquifer initially showed the same pattern Meckenstock et al, 2000). However, a more recent study with the same culture and deuterated naphthalene demonstrated that the initial attack on the parent substrate was methylation to 2-methylnaphthalene, which was subsequently oxidized to 2-naphthoic acid via a fumarate addition reaction (Safinowski and Meckenstock, 2006). The report of naphthalene methylation resembles the recently described methylation of benzene (Ulrich et al, 2005).…”
Section: Discussionmentioning
confidence: 85%
“…However, if we suppose that the carboxylic acid group containing 13 C that we detected was formed after methylation and subsequent oxidation via fumarate addition, in a manner analogous to naphthalene metabolism (Safinowski and Meckenstock, 2006), we would then have to postulate that an isotopically heavy 13 CH 3 group be formed from the labeled bicarbonate. This prospect is at least theoretically possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with M S(0) being the amount of 13 C [mmol] added to the bottle at t ¼ 0 d, the first-order rate constant l, and the reciprocal value of the retardation factor 1/F R designating the fraction of contaminant present in the water phase of the microcosms (Schwarzenbach et al, 2003). For hydrophobic compounds such as BTEX and PAH, the correction by F R is necessary to account for sorption to the sediment matrix since only the dissolved compound fraction is readily available for biodegradation.…”
Section: Inorganic Carbon Mass Balancementioning
confidence: 99%
“…Organic carbon-normalized distribution coefficients K OC were predicted from compound class-specific log K OC À log K OW relationships (Schwarzenbach et al, 2003) taking octanolewater coefficients K OW from the Physical Properties Database (SRC Inc., 2009). Half-life times t 1/2 and half-concentration distances x 1/2 were defined as follows:…”
mentioning
confidence: 99%